Forests, illegality, and livelihoods in Cameroon - Cerutti, P.O.; Tacconi, L. (Center for International Forestry Research, 2006)
Concern about illegal logging has grown considerably over the past decade due to the interest in its environmental impacts, and more recently as a result of its perceived impacts on livelihoods. The authors find that the reality of illegal logging is much more nuanced than has been depicted and that there is a need to focus on illegal forest activities (IFAs) beyond just illegal harvest. This paper shows that the illegal log harvest in Cameroon is smaller than previously thought and that, in recent years, small-scale operators forced to operate illegally by an illicit ministerial decision contributed a significant share. This paper provides suggestions to the government and donor community about priority areas for interventions related to IFAs, sustainability, and livelihoods. These include allowing small-scale logging operations as a way to reverse the historical marginalization of rural people and reducing the misuse of the forest area tax, which is supposed to benefit rural communities.